Engaging religious actors in addressing famine emergencies - Katherine Marshall; Mohammed Abu-Nimer; Cole Durham; Manoj Kurian; Ulrich Nitschke; Arnhild Spence; Rabbi Awraham Soetendorp (Kiel Institute for the World Economy (IfW), 2018)
The United Nations in February 2017 declared a famine emergency in light of the imminent danger of starvation facing an estimated 20 million people in four countries, and appealed urgently for US4 billion to meet immediate needs. Other countries face grave food shortages that present urgent humanitarian needs and undermine long term prospects for peace and development. A feature of contemporary hunger crises is their tight links to conflicts. Religious institutions and leaders are actively involved in the immediate and specific famine situation affecting African nations and Yemen and in efforts to end the conflicts that are the primary cause of famine. More broadly, religious leaders are acting to achieve the United Nations Sustainable Development Goal (SDG) 2, Zero Hunger, by 2030. The imperative to act on hunger is shared across religious divides, and the common purpose that binds different religious communities portends well for peacebuilding and progress in the affected areas. Religious actors should thus be an integral part of the international response to famine emergencies as well as to the Zero Hunger challenge. The urgent crises are pertinent for G20 members and should be prominent on G20 agendas. G20 attention and support to religious roles could enhance responses to the famine and peacebuilding in affected areas and thus contribute to unlocking the potential of the affected countries. Interfaith and intrafaith action on SDG 2, highlighted as part of the global agenda, can speed progress towards Zero Hunger.
Keywords: Q18; 330; Famine; Sustainable Development Goals; Zero Hunger; Starvation; Catholic; Muslim; South Sudan; Nigeria; Somalia; Yemen; Myanmar; Rohingya; Interfaith